The Source of Stress of Students During Pandemic COVID-19: a Qualitative Study - Susan Fitriyana; Titik Respati; Dewi Sartika (Universitas Islam Bandung, 2021)
The COVID-19 pandemic can lead to students' mental health problems, such as anxiety, depression, and stress. The government's policy for study from home exacerbates mental health problems. This study aimed to determine the source of student stress during the study from home during the COVID-19 pandemic. The study design used qualitative research. The sampling technique uses consecutive sampling. This research involved 36 students from the faculty of psychology and the faculty of medicine in Bandung city who underwent study from home (SFH). Data were collected by interviewing participants in May 2020. This study's results are the dominant thing that participants feel during the study from home is boredom, relaxed, and complicated; the things they missed during learning at home were friends, playing, and chatting; and they feel fear, sadness, and anxiety when heard the news about COVID-19. This study concludes that the source of student stress was being far from friends, limited communication and face-to-face contact with friends and lecturers, and did not get direct attention from friends or lecturers. SUMBER STRES MAHASISWA SELAMA MASA PANDEMIK COVID-19: PENELITIAN KUALITATIFPandemik COVID-19 dapat mengakibatkan masalah kesehatan mental untuk mahasiswa seperti kecemasan, depresi, dan stress. Kebijakan pemerintah untuk melakukan pendidikan jarak jauh (PJJ) telah memperburuk masalah kesehatan mental. Tujuan dari penelitian ini adalah untuk menentukan sumber stres mahasiswa selama menjalani PJJ di masa pandemik COVID-19. Desain penelitian ini adalah penelitian kualitatif. Metode pengambilan sampel adalah consecutive sampling dengan melibatkan 36 mahasiswa dari fakultas psikologi dan fakultas kedokteran di Kota Bandung yang menjalani PJJ. Data diambil dengan melakukan wawancara kepada partisipan pada bulan Mei 2020. Hasil dari penelitian ini adalah perasaan dominan yang dirasakan partisipan selama PJJ adalah bosan, santai dan tidak praktis; hal yang dirindukan selama masa kuliah di rumah adalah teman, bermain dan mengobrol; dan hal yang terlintas ketika mendengar berita tentang COVID-19 adalah takut, sedih dan cemas. Kesimpulan dari penelitian ini adalah sumber stres mahasiswa adalah merasa jauh dengan teman, komunikasi dan kontak tatap muka dengan teman dan dosen yang terbatas serta tidak mendapatkan perhatian langsung dari teman dan dosen.